The Importance of Business Risk in Setting Audit Fees: Evidence from Cases of Client Misconduct - LYON, JOHN D.; MAHER, MICHAEL W. (Journal of Accounting Research, 2005)
ABSTRACT Previous research provides evidence that, for the clients of a large audit firm, audit clients with higher perceived business risk bear the expected costs of this risk with higher audit fees. We extend the literature, which focuses on the relation between litigation risk and audit fees, by examining alleged client misconduct that is not illegal but possibly increases business risk. In particular, we examine the relation between audit fees and business risk for audit clients doing business in developing countries where bribery of top government officials has been an accepted business practice. We hypothesize that bribery‐paying clients are riskier because of both client business risk and audit business risk. Using data collected from Securities and Exchange Commission filings and audit fee data in the 1970s, before the passage of the Foreign Corrupt Practices Act, we provide evidence that audit fees were higher for clients that disclosed paying bribes. This evidence is consistent with an audit market where auditors assess business risk at the client level, then pass their expected costs to the client in the form of higher audit fees.